Long-acting anti-corrosion zinc-aluminum-magnesium coating and preparation method thereof
By optimizing the zinc-aluminum-magnesium alloy powder and resin system, and combining it with precise preparation processes, the problems of dispersion stability and overall performance of existing zinc-aluminum-magnesium coatings have been solved, enabling the application of long-lasting anti-corrosion and multifunctional coatings, suitable for the protection of metal structures in ships, aircraft, high-speed railways and marine engineering.
Patent Information
- Application Number
- CN202511822827.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-05
- Publication Date
- 2026-03-17
- Estimated Expiration
- 2045-12-05
AI Technical Summary
Existing zinc-aluminum-magnesium coatings have problems in terms of alloy powder dispersion stability, resin system selection, and preparation process control, making it difficult to meet the multi-functional requirements of long-term corrosion protection, waterproofing, fireproofing, stealth, and thermal insulation. In addition, traditional anti-corrosion coatings have limited anti-corrosion life, and zinc powder is too active, making it prone to excessive corrosion.
By employing an optimized zinc-aluminum-magnesium alloy powder composition and particle size, combined with a composite system of polysiloxane resin and fluorocarbon modified resin, and configuring functional pigments, fillers, and additives, a stable coating system is formed through precise preparation process steps, including pre-dispersion, grinding, and filtration.
It achieves a multi-functional synergistic effect of long-term corrosion protection, waterproofing, fireproofing, stealth, and thermal insulation, significantly improving the protective performance of metal structures and making it suitable for shipbuilding, aircraft, high-speed rail, and marine engineering fields.
Smart Images

Figure CN121673940A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of anti-corrosion coating technology, specifically to a long-lasting anti-corrosion zinc-aluminum-magnesium coating and its preparation method. Background Technology
[0002] With the development of modern industry, metal structures are increasingly widely used in ships, aircraft, high-speed railways, marine engineering, and other fields. However, metal structures face serious corrosion problems during use, especially in corrosive environments such as marine environments and industrial atmospheres. Metal corrosion can lead to a decrease in structural strength, a shortened service life, and an increase in safety hazards. Traditional anti-corrosion coatings mainly use zinc-rich primers, which can provide cathodic protection, but have the following shortcomings: The anti-corrosion life is limited, and it usually needs to be repainted after 5-8 years; High activity of single zinc powder can easily lead to excessive corrosion and consumption. Lacking comprehensive protective performance, it is difficult to meet the multi-functional requirements of waterproofing, fireproofing, stealth, and thermal insulation; It has poor compatibility with topcoat and is prone to problems with insufficient interlayer adhesion; In recent years, zinc-aluminum-magnesium alloy coatings have attracted attention due to their excellent anti-corrosion properties. Through the synergistic effect of zinc, aluminum, and magnesium, zinc-aluminum-magnesium alloys can provide more durable cathodic protection and shielding protection. However, existing zinc-aluminum-magnesium coatings still have the following technical problems: The alloy powder exhibits poor dispersion stability in coating systems, and is prone to sedimentation and agglomeration. An inappropriate choice of resin system leads to poor overall performance of the coating film; Inaccurate control of the preparation process affects the stability and application performance of the coating. Lacking a multi-functional design, it is difficult to meet the usage requirements of special fields; Therefore, developing a zinc-aluminum-magnesium coating with multiple functions such as long-lasting corrosion resistance, waterproofing, fireproofing, stealth, and thermal insulation, and establishing a stable and reliable preparation process, is of great significance for improving the protection level of metal structures. Summary of the Invention
[0003] The purpose of this invention is to overcome the shortcomings of the prior art and provide a long-lasting anti-corrosion zinc-aluminum-magnesium coating and its preparation method. This coating achieves multi-functional synergy of long-lasting anti-corrosion, waterproofing, fireproofing, stealth, and heat insulation by optimizing the composition and particle size of zinc-aluminum-magnesium alloy powder, adopting a composite system of polysiloxane resin and fluorocarbon modified resin, and rationally configuring functional pigments, fillers and additives. It is suitable for the protection of metal structures in the fields of ships, aircraft, high-speed rail, and marine engineering.
[0004] To achieve the above objectives, the present invention adopts the following technical solution: A long-lasting anti-corrosion zinc-aluminum-magnesium coating, comprising the following components by weight: 20-35 parts of zinc-aluminum-magnesium alloy powder, wherein the zinc content in the zinc-aluminum-magnesium alloy powder is 65-75% by weight, the aluminum content is 15-25% by weight, and the magnesium content is 5-10% by weight; 15-25 parts of polysiloxane resin; 10-18 parts of fluorocarbon modified resin; 8-15 parts of epoxy resin; 12-20 parts of pigments and fillers; 1-3 parts of dispersant; 0.5-1.5 parts of leveling agent; 0.3-0.8 parts of catalyst; and 30-45 parts of solvent.
[0005] Preferably, the zinc-aluminum-magnesium alloy powder has a particle size of 3-8 micrometers and a flake size ratio of 30-60.
[0006] Preferably, the polysiloxane resin is a methylphenyl polysiloxane resin with a molecular weight of 8000-15000 and a siloxane bond content of 45-55% by weight.
[0007] Preferably, the fluorocarbon modified resin is a polyvinylidene fluoride modified acrylic resin with a fluorine content of 18-25% by weight and a hydroxyl value of 40-60 mg KOH / g.
[0008] Preferably, the pigments and fillers include 5-8 parts of titanium dioxide, 3-6 parts of mica powder, 2-4 parts of hollow glass microspheres, and 2-4 parts of infrared reflective pigment.
[0009] A method for preparing a long-lasting anti-corrosion zinc-aluminum-magnesium coating includes the following steps: Step 1, Pretreatment: Mix zinc-aluminum-magnesium alloy powder with 30-40% of dispersant, and pre-disperse in a disperser with a speed of 800-1200 rpm for 15-25 minutes to obtain a pre-dispersed slurry; Step 2, Preparation of base material: Mix 50-60% of polysiloxane resin, fluorocarbon modified resin, epoxy resin and solvent in a stirrer with a speed of 300-500 rpm, and control the temperature at 25-35℃ to obtain mixed resin base material. Step 3, grinding and dispersing: Add the pre-dispersed slurry, pigments and fillers and the remaining dispersant to the mixed resin base, grind in a sand mill with zirconium beads as the grinding media, grind for 60-90 minutes, and control the fineness of the output to 20-30 microns. Step 4, Preparation: Add catalyst, leveling agent and remaining solvent to the grinding material, and mix in a stirrer at 200-400 rpm for 20-30 minutes, with the temperature controlled at 20-30℃. Step 5, filtration and packaging: Filter the prepared coating through a filter with a pore size of 60-80 mesh to obtain a long-lasting anti-corrosion zinc-aluminum-magnesium coating.
[0010] Preferably, the pre-dispersion temperature in step one is controlled at 15-25℃, and zinc-aluminum-magnesium alloy powder is added in batches during the pre-dispersion process, with each batch accounting for 20-30% of the total amount.
[0011] Preferably, the grinding temperature in step three is controlled at 35-45℃, the speed of the sand mill is 1500-2000 rpm, and the diameter of the zirconium beads is 0.8-1.2 mm.
[0012] Preferably, the catalyst is added in two parts in step four. The first part is 40-50% of the total amount, and the remaining amount is added after stirring for 10-15 minutes.
[0013] Preferably, in step five, after filtration, the material is allowed to stand for degassing for 8-12 hours, while the temperature is maintained at 18-25℃.
[0014] Compared with the prior art, the beneficial effects of the present invention by adopting the above technical solution are as follows: 1. This invention is approved; 2. This invention is approved; 3. This invention is successful. Attached Figure Description
[0015] Figure 1 This is a process flow diagram for preparing the long-lasting anti-corrosion zinc-aluminum-magnesium coating of the present invention; Figure 2 This is a schematic diagram illustrating the anti-corrosion mechanism of the long-lasting anti-corrosion zinc-aluminum-magnesium coating of the present invention; Figure 3 This is a schematic diagram of the microstructure of the coating film of the present invention. Detailed Implementation
[0016] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0017] Example 1 A long-lasting anti-corrosion zinc-aluminum-magnesium coating, comprising the following components by weight: 28 parts of zinc-aluminum-magnesium alloy powder (zinc content 70 wt%, aluminum content 20 wt%, magnesium content 7.5 wt%, particle size 5 micrometers, flake size ratio 45); 20 parts of methylphenyl polysiloxane resin (molecular weight 12000, siloxane bond content 50% by weight); 14 parts of polyvinylidene fluoride modified acrylic resin (fluorine content 22% by weight, hydroxyl value 50mgKOH / g). 12 parts epoxy resin (bisphenol A type epoxy resin, epoxy value 0.51); 6.5 parts titanium dioxide (rutile type); 4.5 parts mica powder (flake diameter 30-50 micrometers); Three portions of hollow glass microspheres (particle size 20-80 micrometers, density 0.25 g / cm³) 3 ); Three parts of infrared reflective pigment (aluminum titanate-based composite pigment); 2 parts dispersant (polyamide wax dispersant); 1 part leveling agent (modified polyacrylate); 0.5 parts catalyst (organotin catalyst); 38 parts solvent (a mixed solvent of xylene and butyl ester in a mass ratio of 1:1).
[0018] The preparation method includes the following steps: Step 1, Pretreatment: Mix 28 parts of zinc-aluminum-magnesium alloy powder with 0.8 parts of dispersant, and pre-disperse in a high-speed disperser at 1000 rpm for 20 minutes, with the temperature controlled at 20℃. Add the zinc-aluminum-magnesium alloy powder in three batches, with each batch adding 25%, 35%, and 40% of the total amount, to obtain a pre-dispersed slurry.
[0019] Step 2, Preparation of base material: Mix 20 parts of methylphenyl polysiloxane resin, 14 parts of polyvinylidene fluoride modified acrylic resin, 12 parts of epoxy resin and 20 parts of solvent (11 parts of xylene and 9 parts of butyl ester) evenly in a stirrer at a speed of 400 rpm, control the temperature at 30℃, and stir for 45 minutes to obtain a mixed resin base material.
[0020] Step 3, Grinding and Dispersion: Add the pre-dispersed slurry, 6.5 parts titanium dioxide, 4.5 parts mica powder, 3 parts hollow glass microspheres, 3 parts infrared reflective pigment and 1.2 parts remaining dispersant to the mixed resin base, grind in a sand mill with 1.0 mm diameter zirconium beads as the grinding media, the sand mill speed is 1800 rpm, the grinding temperature is controlled at 40℃, the grinding time is 75 minutes, and the output fineness is 25 microns.
[0021] Step 4, Preparation: First, add 0.25 parts of catalyst (50% of the total amount) to the grinding material and stir for 12 minutes in a stirrer at 300 rpm. Then, add the remaining 0.25 parts of catalyst, 1 part of leveling agent and 18 parts of solvent (9 parts xylene and 9 parts butyl ester), and continue stirring for 25 minutes, keeping the temperature at 25℃.
[0022] Step 5, filtration and packaging: Filter the prepared coating through a 70-mesh filter, then let it stand for 10 hours to remove bubbles, while maintaining the temperature at 22℃, to obtain a long-lasting anti-corrosion zinc-aluminum-magnesium coating.
[0023] Performance test results: Appearance: Uniform gray paint, without lumps; Viscosity (Ford Cup 4, 25°C): 85 seconds; Fineness: ≤25 micrometers; Drying time (25℃): Surface dry in 2 hours, fully dry in 24 hours; Coating thickness: 80 micrometers; Adhesion (cross-cut test): Level 1; Flexibility: 1mm; Salt spray resistance (neutral salt spray, GB / T 1771): No blistering, rusting, or peeling after 3500 hours; Weather resistance (xenon lamp aging, GB / T 1865): 2200 hours, gloss loss ≤15%, chalking ≤1 level; Contact angle: 110 degrees; Water absorption rate (24 hours): 0.6%; Temperature resistance: After maintaining 420℃ for 2 hours, the coating showed no cracking or peeling. Oxygen index: 30; Infrared emissivity: 0.4; Thermal conductivity: 0.06 W / (m·K).
[0024] Example 2 A long-lasting anti-corrosion zinc-aluminum-magnesium coating, comprising the following components by weight: 23 parts of zinc-aluminum-magnesium alloy powder (zinc content 68 wt%, aluminum content 22 wt%, magnesium content 6 wt%, particle size 4 micrometers, flake size ratio 40); 18 parts of methylphenyl polysiloxane resin (molecular weight 10000, siloxane bond content 48% by weight); 12 parts of polyvinylidene fluoride modified acrylic resin (fluorine content 20% by weight, hydroxyl value 45 mg KOH / g). 10 parts epoxy resin (bisphenol A type epoxy resin, epoxy value 0.51); 6 parts titanium dioxide; 4 parts mica powder; 2.5 parts of hollow glass microspheres; 2.5 parts of infrared reflective pigment; 1.5 parts dispersant; 0.8 parts leveling agent; 0.4 parts catalyst; 42 parts solvent (a mixed solvent of xylene and butyl ester in a mass ratio of 1:1).
[0025] The preparation method is the same as in Example 1, with specific parameters adjusted as appropriate: the pre-dispersion speed is 900 rpm, the pre-dispersion time is 18 minutes, the grinding time is 70 minutes, the output fineness is 22 microns, and the standing time is 9 hours.
[0026] Performance test results: Appearance: Uniform gray paint, without lumps; Viscosity (Ford Cup 4, 25°C): 78 seconds; Fineness: ≤22 micrometers; Drying time (25℃): Surface dry 2.5 hours, fully dry 24 hours; Coating thickness: 75 micrometers; Adhesion (cross-cut test): Level 1; Flexibility: 1mm; Salt spray resistance: No blistering, rusting, or peeling after 3200 hours; Weather resistance: 2000 hours, gloss loss ≤18%, chalking ≤1 level; Contact angle: 108 degrees; Water absorption rate: 0.7%; Temperature resistance: After maintaining 400℃ for 2 hours, the coating showed no cracking or peeling. Oxygen index: 29; Infrared emissivity: 0.42; Thermal conductivity: 0.07 W / (m·K).
[0027] Example 3 A long-lasting anti-corrosion zinc-aluminum-magnesium coating, comprising the following components by weight: 32 parts of zinc-aluminum-magnesium alloy powder (zinc content 72 wt%, aluminum content 18 wt%, magnesium content 8 wt%, particle size 6 micrometers, flake size ratio 50); 22 parts of methylphenyl polysiloxane resin (molecular weight 13000, siloxane bond content 52% by weight); 16 parts of polyvinylidene fluoride modified acrylic resin (fluorine content 23% by weight, hydroxyl value 55mgKOH / g). 13 parts epoxy resin; 7 parts titanium dioxide; 5 parts mica powder; 3.5 parts of hollow glass microspheres; 3.5 parts of infrared reflective pigment; 2.5 parts dispersant; Leveling agent 1.2 parts; 0.6 parts catalyst; 35 parts solvent.
[0028] The preparation method is the same as in Example 1, with specific parameters adjusted as appropriate: the pre-dispersion speed is 1100 rpm, the pre-dispersion time is 23 minutes, the grinding time is 80 minutes, the output fineness is 28 micrometers, and the standing time is 11 hours.
[0029] Performance test results: Appearance: Uniform gray paint, without lumps; Viscosity (Ford Cup 4, 25°C): 92 seconds; Fineness: ≤28 micrometers; Drying time (25℃): Surface dry 1.8 hours, fully dry 22 hours; Coating thickness: 85 micrometers; Adhesion (cross-cut test): Level 1; Flexibility: 1mm; Salt spray resistance: No blistering, rusting, or peeling after 3800 hours; Weather resistance: 2400 hours, gloss loss ≤12%, chalking ≤1 level; Contact angle: 112 degrees; Water absorption rate: 0.5%; Temperature resistance: After maintaining 430℃ for 2 hours, the coating showed no cracking or peeling. Oxygen index: 31; Infrared emissivity: 0.38; Thermal conductivity: 0.05 W / (m·K).
[0030] Comparative Example 1 A conventional zinc-rich primer, by weight, comprises the following components: 55 parts zinc powder; 25 parts epoxy resin; 12 parts of curing agent; 5 parts pigments and fillers; 1 part of the auxiliary agent; 30 parts solvent.
[0031] Preparation method: Mix epoxy resin, pigments, fillers, additives and solvents, add zinc powder and grind to disperse, add curing agent to adjust, filter and package.
[0032] Performance test results: Salt spray resistance: 1500 hours; Weather resistance: 800 hours; Contact angle: 85 degrees; Water absorption rate: 2.5%; Temperature resistance: 250℃; It lacks both stealth and thermal insulation functions.
[0033] Comparative Example 2 A zinc-aluminum coating (magnesium-free) comprises the following components by weight: 30 parts of zinc-aluminum alloy powder (zinc content 85% by weight, aluminum content 15% by weight); 20 parts of polysiloxane resin; 12 parts epoxy resin; 10 parts pigments and fillers; Two parts of the auxiliary agent; Solvent 40 parts.
[0034] The preparation method is the same as in Example 1.
[0035] Performance test results: Salt spray resistance: 2200 hours; Weather resistance: 1200 hours; Contact angle: 95 degrees; Water absorption rate: 1.5%; Temperature resistance: 350℃; The alloy powder has insufficient activity, resulting in limited improvement in corrosion resistance.
[0036] The comparison between Examples 1-3 and Comparative Examples 1-2 shows that the long-lasting anti-corrosion zinc-aluminum-magnesium coating of the present invention is significantly superior to the prior art in terms of anti-corrosion performance, waterproof performance, temperature resistance performance, stealth performance, and thermal insulation performance. It is suitable for metal structure protection in fields such as ships, aircraft, high-speed rail, and marine engineering.
[0037] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A long-lasting anticorrosive zinc-aluminum-magnesium coating comprising a zinc-aluminum-magnesium coating, characterized in that: The zinc-aluminum-magnesium coating comprises the following components in parts by weight: Zinc-aluminum-magnesium alloy powder 20-35 parts, the zinc content in the zinc-aluminum-magnesium alloy powder is 65-75% by weight, the aluminum content is 15-25% by weight, and the magnesium content is 5-10% by weight; Polysiloxane resin 15-25 parts; Fluorocarbon modified resin 10-18 parts; Epoxy resin 8-15 parts; Color and filler 12-20 parts; Dispersant 1-3 parts; Leveling agent 0.5-1.5 parts; Catalyst 0.3-0.8 parts; Solvent 30-45 parts.
2. The long-acting anticorrosive zinc-aluminum-magnesium coating material according to claim 1, characterized by: The particle size of the zinc-aluminum-magnesium alloy powder is 3-8 microns, and the flake diameter ratio is 30-60.
3. The long-acting anticorrosive zinc-aluminum-magnesium coating material according to claim 1, characterized in that: The polysiloxane resin is methylphenyl polysiloxane resin with a molecular weight of 8000-15000 and a siloxane bond content of 45-55% by weight.
4. The long-acting anticorrosive zinc-aluminum-magnesium coating material according to claim 1, characterized in that: The fluorocarbon modified resin is polyvinylidene fluoride modified acrylic resin with a fluorine content of 18-25% by weight and a hydroxyl value of 40-60 mg KOH / g.
5. The long-lasting anticorrosive zinc-aluminum-magnesium coating material according to claim 1, characterized by: The color and filler includes titanium dioxide 5-8 parts, mica powder 3-6 parts, hollow glass microbeads 2-4 parts, and infrared reflective pigment 2-4 parts.
6. A long-lasting anticorrosive zinc-aluminum-magnesium coating according to claim 1, and a method for its preparation, comprising a method for its preparation, characterized by: The preparation method comprises the following steps: Step one, pretreatment: mix the zinc-aluminum-magnesium alloy powder with 30-40% of the dispersant, pre-disperse in a disperser at a speed of 800-1200 rpm for 15-25 minutes to obtain a pre-dispersed slurry; Step two, prepare the base: mix 50-60% of the polysiloxane resin, fluorocarbon modified resin, epoxy resin, and solvent in a stirrer at a speed of 300-500 rpm, control the temperature at 25-35°C, and obtain a mixed resin base; Step three, grind and disperse: add the pre-dispersed slurry, color and filler, and the remaining dispersant to the mixed resin base, grind in a sand mill, the grinding medium is zirconium beads, the grinding time is 60-90 minutes, and the discharge fineness is controlled at 20-30 microns; Step four, adjust: add the catalyst, leveling agent, and remaining solvent to the ground material, mix in a stirrer at a speed of 200-400 rpm for 20-30 minutes, and control the temperature at 20-30°C; Step five, filter and package: filter the adjusted coating through a filter screen with a pore size of 60-80 mesh to obtain a long-acting anticorrosive zinc-aluminum-magnesium coating.
7. The long-lasting anticorrosive zinc-aluminum-magnesium coating material and the preparation method thereof according to claim 1, characterized in that: The pre-dispersing temperature in step one is controlled at 15-25°C, and the zinc-aluminum-magnesium alloy powder is added in batches during the pre-dispersing process, with each batch accounting for 20-30% of the total amount.
8. The long-lasting anticorrosive zinc-aluminum-magnesium coating material and the preparation method thereof according to claim 1, characterized in that: The grinding temperature in step three is controlled at 35-45°C, the speed of the sand mill is 1500-2000 rpm, and the diameter of the zirconium beads is 0.8-1.2 mm.
9. The long-lasting anticorrosive zinc-aluminum-magnesium coating material and the preparation method thereof according to claim 1, characterized in that: The catalyst in step four is added in two batches, with 40-50% of the total amount added first, and the remaining amount added after stirring for 10-15 minutes.
10. The long-lasting anticorrosive zinc-aluminum-magnesium coating material and the preparation method thereof according to claim 1, characterized in that: After filtering in step five, perform static defoaming treatment, with a static time of 8-12 hours and a temperature maintained at 18-25°C.
Citation Information
Patent Citations
Nano zinc aluminum modified epoxy-fluorocarbon coating
CN101007922A
Organic / inorganic composite heat-insulating heat-preserving water-based building coating and preparation method thereof
CN102399483A
Fluororesin modified high-chlorinated polyethylene fireproof anticorrosion composite coating
CN103555077A
Electro-conductive thermoplastic resin compositions and articles manufactured therefrom
EP2176335A1
Resin composition and molded article comprising the same
JP2008001766A